ANALISIS PENGADAAN LOGISTIK ALAT KESEHATAN DI RSUD dr. RASIDIN PADANG - Aini, Rafika; Sari, Mila; Aulia, Mirza; Leonard, Devid (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
The procurement of medical equipment is part of hospital logistics management to meet user needs and improve service quality. RSUD dr. Rasidin Padang has implemented this function, but challenges remain, such as unutilized medical equipment post-procurement. This study aims to analyze the procurement of medical equipment logistics at RSUD dr. Rasidin. In the input component, the IPSRS workforce consists of 6 staff members, but their capacity is limited due to a lack of formal training and the absence of SOPs. In the process component, planning is conducted annually based on user requests, with procurement carried out through e-catalogs or vendors. In the output component, the results are suboptimal due to insufficient coordination and equipment utilization. The study concludes that improvements in staff training, SOP development, and inter-unit coordination are needed to enhance procurement efficiency and hospital services.Keywords: Procurement, Logistics, Medical Equipment